Gorbachev and Reagan the last superpower summits : conversations that ended the Cold War - Savranskaya, Svetlana; Blanton, Thomas S.; Melyakova, Anna (National Security Archive Cold War readers., 2020)
"This book is the culmination of twenty years of research in which the editors gathered thousands of pages documenting the most important conversations of the late Cold War. Every word Ronald Reagan and Mikhail Gorbachev said to each other in their five superpower summits from 1985 to 1988 is included in this volume. The editors argue in their contextual essays and detailed notes that these summits fueled a learning process on both sides of the Cold War. Their anthology provides insight into the nuanced shifts of monumentally important discussions, showing how Moscow's sense of threat was eased and how a hawkish Reagan softened his tone in negotiations during his second presidential term. Documents from foreign ministers Eduard Shevardnadze and George Shultz offer a particularly intriguing look into the handful of conversations that ended almost half a century of conflict. These verbatim transcripts, until now top secret, are combined with fascinating photos and crucial information from declassified preparatory and after-action documents from both the Americans and Soviets, obtained in the US through the Freedom of Information Act and in Russia from the Gorbachev Foundation, the State Archive of the Russian Federation in Moscow, and from the personal files of Anatoly Chernyaev, Gorbachev's foreign policy adviser"--